Avaliação do processo de produção de colorante natural vermelho pelo fungo endofítico Talaromyces minnesotensis - Sousa, Marina Del Bianco (2022)
The growing incentive and awareness regarding the consumption and use of more sustainable proposals, biocolorants from filamentous fungi are presented as a promising alternative to synthetic colorants. These biocompounds are less harmful to living beings and the environment, presenting greater stability and biotechnological potential compared to other natural sources. In this context, this thesis aimed to characterize the red biocolorant synthesized by the endophytic fungus Talaromyces minnesotensis, as well as to evaluate the biocolorant production process in shaken flasks and in conventional bioreactors, aiming the improvement of the bioprocess. Initially, the endophytic fungus T. minnesotensis was phenotypically characterized by assays carried out in different solid media. Then, its potential for biocolorant production was verified through submerged cultures in shaken flasks. The synthesized biocolorant was characterized by means of fluorescence, cytotoxicity (MTT and MIC), stability, and applicability assays. The characterization and application tests showed that the biocolorant has activity against human hepatoblastoma cells (HepG2) at concentrations above 5.0 g L-1, while for pathogenic bacteria and yeasts the concentration must be higher than 50.0 g L-1. In addition, the bioproduct showed high stability at neutral pH values (6 to 8) and at low temperatures (10 to 20°C). Expressive coloring potential of the red biocolorant produced in different matrices such as detergent, gelatin, enamel, paint, and fabrics, was also verified, which indicates the feasibility of a more in-depth study of the bioprocess to improve and increase its production. Thus, a factorial design (22 +3PC) was performed, aiming to evaluate the influence of three combinations of impellers of different geometries under different conditions of agitation frequency (400-800 rpm) and specific air supply flow rate (0, 5-1.5 vvm) on the production of biocolorant in a conventional bioreactor. The results were analyzed based on the Global Desirability (DG) in terms of the main response variables of performance, production, and productivity of biocolorant. It was shown that the configuration composed of two elephant ear impellers (EEDP-EEUP) operated at 600 rpm and 1.0 vvm was the most favorable to the bioprocess, obtaining a production of 45.30 AU. By correlations assessment, it was verified that the hydrodynamic properties tended to present greater relevance to the performance of the bioprocess compared to the oxygen transfer properties. In order to evaluate the performance of the bioprocess on a larger scale, an exploratory study was carried out to scale up the bioprocess from 4 to 10 L bioreactor, in which a satisfactory result was obtained by reaching an equal production for both scales. Finally, in order to improve the production of biocolorant, the use of the fed-batch mode in shaken flasks and in a conventional bioreactor was evaluated. The production in these assays reached expressive results for both scales: a maximum production of the order of 86.0 AU in shaken flasks, and maximum production ranged from 80 to 238% in relation to the conventional batch for bioreactors. Regarding this last, the increase of production depended on the feeding conditions (FCSF), reaching a maximum production of approximately 153.0 AU in the most favorable condition at a feeding flow rate of 0.01 L h-1 (F) and a substrate concentration of 60 gS L-1 (CSF). These results proved the fact the bioprocess production of colorant by the endophytic fungus T. minnesotensis has a high potential for future studies aiming for its implementation at pilot and industrial scales.